Psychosocial support for people with dementia with Lewy bodies. (2nd May 2021) - Killen, Alison
Abstract : Background: Lewy body dementia is the second most common form of age-related neurodegenerative dementia. It has two forms: dementia with Lewy bodies and Parkinson's disease dementia. Methods: There are specific core symptoms associated with dementia with Lewy bodies. Optimum care requires awareness of the features associated with these, as well as appropriate support and management strategies, which are provided in this article. Results: The core features of dementia with Lewy bodies are visual hallucinations, cognitive fluctuations, Parkinsonism and rapid eye movement sleep behaviour disorder. Appropriate psychosocial strategies includes psychoeducation, social support and environmental modification. Adoption of these approaches can reduce adverse outcomes. Conclusions: The core features of dementia with Lewy bodies can significantly impair quality of life. Nursing and residential care staff are ideally placed to address this through the implementation of psychosocial strategies both directly, and through the provision of psychoeducation for family caregivers.